2011
DOI: 10.1016/j.jcrs.2010.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Vertical versus oblique implantation of intrastromal corneal ring segments for keratoconus

Abstract: Neither author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 7 publications
0
19
1
1
Order By: Relevance
“…Incision location was chosen based on the corneal topographic steep meridian. 26 All Kerarings were implanted by the same surgeon (MRS).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Incision location was chosen based on the corneal topographic steep meridian. 26 All Kerarings were implanted by the same surgeon (MRS).…”
Section: Surgical Techniquementioning
confidence: 99%
“…20 In order to obtain the optimal clinical outcomes after the ICRS implantation, each manufacture provides a specific nomogram to help clinicians select the best ring characteristics according to clinical data. The available nomograms A c c e p t e d M a n u s c r i p t 5 were mainly developed based on the distribution of ectatic corneal region, its symmetry status, and the spherical/cylindrical components of refractive error, while other factors such as preoperative visual acuity, 9 mean keratometry, corneal topographic pattern, 21 keratoconus grading, 15,22,23 aberrations, 10 coincidence between refractive, topographic and comatic axes, 24,25 incision location, 24,26 corneal biomechanical properties, 22,27,28 and internal astigmatism 15 may affect the surgical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,[13][14][15][16][17] The meridian chosen for the incision site has been defined in relation to the location of the positive refractive cylinder axis or the keratometric steep meridian. 17 From earlier studies in which the 14 surgeons have continued to modify their approaches to improve outcomes. 7,15,16,A Sedaghat and Zarei-Ghanavati 17 compared refractive outcomes and visual acuity after insertion of paired Ferrara rings (Ferrara Ophthalmics) in 2 groups of patients with keratoconus, 1 with vertical (between 70 degrees and 110 degrees) paired segments and the other with oblique paired segments.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that eyes with a preoperative steep vertical topographic axis had a more favorable outcome and suggested that eyes with oblique corneal astigmatism have reduced biomechanical properties, resulting in less correction of corneal irregularity after vertical implantation of ICRS. 17 Piñero et al 19 identified a deficiency in many studies of ICRS that found significant reductions in astigmatism in keratoconic corneas, namely an absence of analysis of changes in the axis of astigmatism. The authors used the Alpins method of vectorial analysis to study corneal astigmatic changes after ICRS (Kerarings, Mediphacos) insertion.…”
Section: Discussionmentioning
confidence: 99%
“…24 İmplantasyon planlanan korneada merkezi skarın olmaması ve segmentin geçeceği bölgede kornea kalınlığının en az 400 µm olması gerekir. 25,26 Anlamlı fonksiyonel görme artışı sağlanamadığından çok ileri evredeki keratokonusta (K maks 70 D üzeri), kaşımayla segmentte migrasyon ve ekstrüzyon olasılığı artığından ciddi ve kontrol altına alınmamış vernal keratokonjonktivitte, artmış korneal erozyon olasılığı nedeni ile rekürrens epitel erozyon sendromu olan hastalarda, görsel sonuçlar hakkında yüksek beklentisi olan hastalarda ve otoimmün hastalığı olan hastalarda segment implantasyonu uygun değildir. 27,28 Ayrıca skotopik pupil çapı segmentin çapından daha geniş olan hastalar gece gelişebilecek halo ve glare konusunda uyarılmalıdır.…”
Section: Endi̇kasyonlar/kontrendi̇kasyonlarunclassified